Handbook of research on entrepreneurship and marketing for global reach in the digital economy - Carvalho, Luisa Cagica, 1970-; Isaias, Pedro (Business Science Reference, 2019)
"This book addresses the main issues of interest within the topics of entrepreneurship and marketing in digital world. It emphasizes emergent and innovative aspects of digital marketing strategies and entrepreneurial approaches to overcome the challenges of the digital world. It discusses innovative studies as key developments such as digital marketing, digital entrepreneurship, e-Business, e-Commerce, and social networks"--